Pellacalyx Symphiodiscus STAFP FROM LONG BAGUN, MAHAKAM HULU: MORPHOLOGICAL CHARACTERIZATION AND ITS DISTRIBUTION [Pellacalyx Symphiodiscus Stafp dari Long Bagun, Mahakam hulu: Karakretisai Morfologi dan Persebarannya] - Astuti, Inggit Puji; Susandarini, Ratna; Sari, Rismita (Research Center for Biology-Indonesian Institute of Sciences, 2017)
Pellacalyx is one of the genera in Rhizophoraceae, distributed from Myanmar, South China, Indonesia, Malaysia and the Philippines. In Indonesia, Pellacalyx can be found in the island of Sumatra, Kalimantan and Sulawesi. Eight species of Pellacalyx have been found Â in Indonesia, four of which them were from Kalimantan, i.e. P. axillaris, P. cristatus, P. lobbii and P. symphiodiscus. These four species generally grow in the primary and secondary forest, from lowland to an altitude of 1300 m above sea level. Information of Pellacalyx in Indonesia is still very limited , and rarely found in the wild. The last information of Pellacalyx found in West Sumatra was reported by an expedition team of the Center for Plant Conservation Bogor Botanical Garden in 2006. Â The Expert Team of the Khatulistiwa Expedition in Long Bagun, West Kutai, East Kalimantan on May 26âJune 2, 2012 found a species of Pellacalyx. Morphological characterization was then conducted based on the herbarium specimen for identification. The identification was carried out in Bogor Botanic Gardens, Center for Biological Research, Indonesian Institute of Sciences and The National Herbarium Leiden, Netherland. The results show that Pellacalyx specimen from Long Bagun is Pellacalyx symphiodiscus.Â